Сохранение ТПР в Автономной республики Крым, как резерв повышения инвестиционной активности - Севастьянова, О.В. (Культура народов Причерноморья, 2005)
The problem of the investment in the Autonomous Republic of Crimea are highlighted, the analysis of the main factors characterizing the functions of the territories of the priority development is made, the reserves of the increasing of the investment into the recreation - tourist sphere of the ARK are found.